1979
DOI: 10.1111/j.1476-5381.1979.tb10844.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional Antagonism as a Means of Determining Dissociation Constants and Relative Efficacies of Sympathomimetic Amines in Guinea‐pig Isolated Atria

Abstract: I The positive inotropic and chronotropic responses to sympathomimetic amines were examined in guinea-pig isolated atria.2 The order of potency measured from EC3o values was isoprenaline > orciprenaline > salbutamol > fenoterol > terbutaline. Terbutaline and salbutamol were partial agonists on rate and together with orciprenaline and fenoterol also on tension responses. 3 Functional antagonism by carbachol caused a rightwards shift of the dose-response curve and depression of the maximum response. The rate max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

1981
1981
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 22 publications
3
16
0
Order By: Relevance
“…These differences and the KA values themselves compare favourably with the values obtained by functional antagonism (Broadley & Nicholson, 1979). Differences in KA value and potency of agonists can be modified by factors that affect their concentration in the vicinity of the receptor.…”
Section: Discussionsupporting
confidence: 53%
“…These differences and the KA values themselves compare favourably with the values obtained by functional antagonism (Broadley & Nicholson, 1979). Differences in KA value and potency of agonists can be modified by factors that affect their concentration in the vicinity of the receptor.…”
Section: Discussionsupporting
confidence: 53%
“…(e.g. Buckner & Saini, 1975;Broadley & Nicholson, 1979;Broadley & McNeill, 1983). This is exemplified in Figure 6 by the data of Buckner & Saini (1975 (Kaumann, 1978;Hedberg & Mattson, 1981), rat lung (Minneman et al, 1979) and human cardiac muscle (Stiles et al, 1983) (2) and (3)).…”
Section: Discussionmentioning
confidence: 84%
“…For example, the application of a specific irreversible antagonist (Furchgott, 1966) can be assumed simply to reduce the functional receptor concentration, so that equal agonist effects in the presence and absence ofthe antagonist reflect equal concentrations ofAR. It has also been suggested that functional antagonism (Buckner & Saini, 1975;Broadley & Nicholson, 1979) and other post-receptor interventions (Giao T. Rico, 1971a,b) may be used to quantify agonism. However, these procedures deliberately change the transducer machinery and there seems to be no a priori reason why they should allow reliable quantification of agonist affinity and efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…More recently the technique suggested by Buckner & Saini (1975) has been used by Broadley & Nicholson (1979) who reached the surprising conclusion that several drugs, normally thought of as partial agonists at (3-adrenoceptors, had intrinsic efficacies greater than that of isoprenaline in producing positive chronotropic responses on guinea-pig isolated atria. If the functional antagonism is not type IIA then KA may be overestimated and this overestimation would be expected to be greater for those agonists with higher intrinsic efficacies.…”
Section: Theory Derivation Ofnull Equations Forfunctional Interactionmentioning
confidence: 99%